Novel Pathogenesis and Treatments for Cardiovascular Disease - Gaze, David C. (IntechOpen, 2023)
This book provides a comprehensive overview of cardiovascular diseases (CVDs) and associated conditions. It is organized into three sections on "Cardiovascular Pathophysiology", "Cardiovascular Diagnostics", and "Cardiovascular Treatments". Chapters address such topics as the role of obesity in CVD, cardiotoxicity, cardio-oncology, CVD in different disease states, modalities for detecting CVD, interventional strategies to prevent or treat CVD, and much more.